Agricultural dust explosions in 2002 - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
There were eight dust explosions reported in the U.S. in 2002 according to Robert W. Schoeff, Professor Emeritus, Kansas State University, and Mavis Rogers, FGIS-USDA. This compares to 9 in 2001 and a tenyear average of 12.2 explosions.
Keywords: Grain dust; Dust explosions